Food research: nutritional anthropology and archaeological methods - Chrzan, Janet; Brett, John (Research methods for anthropological studies of food and nutrition, 2017)
Biocultural and archaeological research on food, past and present, often relies on very specific, precise, methods for data collection and analysis. These are presented here in a broad-based review. Individual chapters provide opportunities to think through the adoption of methods by reviewing the history of their use along with a discussion of research conducted using those methods. A case study from the author's own work is included in each chapter to illustrate why the methods were adopted in that particular case along with abundant additional resources to further develop and explore those methods.